Implementasi Hukum Adat Dalam Upaya Integrasi Pengendalian Pencemaran Lingkungan Terhadap Hukum Positif (Studi Kasus Desa Ngadirojo, Sokoo, Ponorogo) - Adji Samudera Trisnatyan Pamadi; Linda Gusnia R (Legal Standing : Jurnal Ilmu Hukum, 2017)
Today's environmental pollution control has been set in national law. Through the Environmental Management and Protection Act No. 32 of 2009 it was explained that environmental pollution is a criminal act. Criminal action in positive law then its prosecution through imprisonment. In contrast to people who still have customary law, which is customary law used as a solution to legal problems. A contribution of society to support the retributive pattern. Optimizing the role of society and customary law into a replacement solution of existing imprisonment. Bids fines become a reference for developing an integrated pattern of society. The involvement of the community to be proactive with all actions or efforts of environmental pollution from certain parties become the commodity of emphasis of environmental pollution in order to keep the naturally. Customary law becomes an identity that is in accordance with the culture of the state of Indonesia and also as an alternative law that exists. The integration between customary law and positive law remains an option in balancing life processes.